(untitled) (Research, Society and Development, 2024)
Psoriasis is a chronic inflammatory disease characterized by immune mediated skin inflammation and hyperproliferation of keratinocytes, resulting in erythematous plaques or papules covered with silvery scales, primarily affecting extensor surfaces, nails, scalp, and trunk, often accompanied by itching and irritation during active phases. It exhibits clinical variability and can manifest in various forms, including plaque, nail, guttate, inverse, pustular, erythrodermic, and psoriatic. This condition has a genetic predisposition, and when combined with environmental and behavioral factors, plays a significant role in disease progression. The prevalence of cardiovascular risk factors and metabolic disorders has been found to be high in psoriasis patients, possibly due to the inflammatory nature common to both conditions. Current studies suggest that the inflammatory nature of psoriasis may be linked to a predisposition to other diseases with altered inflammatory status, particularly cardiovascular diseases. This study aims to provide a synthesis of current and relevant information regarding the association between psoriasis and cardiovascular risk factors. Information was obtained through a systematic review, of a descriptive and exploratory nature, using the PRISMA method, searching for articles in the PubMed and BVS databases with the keywords "Psoriasis," "Cardiovascular disease," and "Risk factors." The review included articles from Controlled Clinical Trials published between 2018 and 2023, demonstrating the connection between psoriasis and cardiovascular damage, as well as the need for further in-depth studies on the subject, as well as methods for screening, prevention, and treatment of cardiovascular risk factors in psoriasis patients.